2018
DOI: 10.1093/ejo/cjy062
|View full text |Cite
|
Sign up to set email alerts
|

Association of facial sagittal and vertical characteristics with facial aesthetics in the Northern Finland Birth Cohort 1966

Abstract: Facial sagittal dimensions appeared to influence facial aesthetics more than vertical dimensions in middle-aged adults. In their perception of facial aesthetics, orthodontists were more influenced by antero-posterior jaw relationships than dentists and laypersons. The overall perception of facial attractiveness related to facial dimensions appeared to differ between the panel groups in female and male faces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…According to the literature, there is a preference for a straight profile that corresponds to a Class I skeletal pattern, 28 which reflects facial attractiveness. 29 Thus, the most likely explanation for our results is that the anteroposterior aspect of the face is considered an important factor in the evaluation of aesthetics, which justifies the impact related to convex (Class II pattern) and concave (Class III pattern) profiles. The results supported the importance of in-depth investigation at the item level of OHRQoL assessment scales.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…According to the literature, there is a preference for a straight profile that corresponds to a Class I skeletal pattern, 28 which reflects facial attractiveness. 29 Thus, the most likely explanation for our results is that the anteroposterior aspect of the face is considered an important factor in the evaluation of aesthetics, which justifies the impact related to convex (Class II pattern) and concave (Class III pattern) profiles. The results supported the importance of in-depth investigation at the item level of OHRQoL assessment scales.…”
Section: Discussionmentioning
confidence: 63%
“…The literature has affirmed that women report greater oral health-related social and psychological impacts than men. 10 , 29 , 30 The main difference in the findings concerned the age range; the majority of studies that have observed greater impacts on women 10 , 29 , 30 evaluated adolescents; in our study, we evaluated young adults.…”
Section: Discussionmentioning
confidence: 92%
“…Studies in the literature indicate that, in this stage, there are better orthopedic responses to correct posterior skeletal crossbite 32 , anterior open bite 33 and skeletal Class III malocclusion 34 , as well as to monitor spaces and diagnose impactions or ectopic teeth. Several randomized con- trolled trials investigating the treatment of Class II malocclusion during growth had similar results for both the two-stage interventions -first at about the age of seven years and then during the time of young permanent dentition -and the one-stage treatment during pubertal growth spurt 18,11,35 .…”
Section: Discussionmentioning
confidence: 86%
“…Dental and skeletal Class II malocclusion carries a greater risk of dental trauma 10 , a more negative perception of facial 11 and dental 12 esthetics, a negative impact on quality of life and self-esteem 13 , a greater predisposition to periodontal diseases 14 and tooth wear 15,16 , and a reduction of oropharyngeal space and greater incidence of sleep disorders 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Contini et al [ 30 ] indicated that the facial balance is not only affected by orthodontic treatment, but also by facial growth. Krooks et al [ 31 ] performed esthetic evaluation of facial attractiveness. They found that facial sagittal dimensions affected more facial esthetics than the vertical dimensions.…”
Section: Discussionmentioning
confidence: 99%